Death in a farmer with underlying diseases carrying Vibrio cholerae non-O1/non-O139 producing zonula occludens toxin - Ying Zhao; Tingting He; Bowen Tu; Xujian Mao; Jingyi Jiang; Xia Jiang; Fengming Wang; Min Wang; Yu Wang; Hongyan Sun (International Journal of Infectious Diseases, 2022)
Objectives: The non-O1/non-O139 Vibrio cholerae caused outbreaks or sporadic cases of gastroenteritis that was rarely seen in good sanitary condition. It was described a case of systemic multiple organ lesions that worsened because of non-O1/non-O139 V. cholerae, suggesting that serogroups have a potential virulence in enhancing pathogenicity with patients with underlying diseases compared with a healthy population. Design or methods: Samples are identified by strain culture, polymerase chain reaction (PCR) virulence identification, and whole genome sequencing. Results: A middle-aged man was diagnosed with cytotoxin-producing and nontoxin V. cholerae non-O1/non-O139 serogroups. Although lacking the CT toxin encoded by ctxAB gene, the pathogenesis of cholera relies on the synergistic action of many other genes, especially virulence genes. Conclusions: This case suggested that the laborers engaging in agricultural production are at potential risk of V. cholerae infection by exposure of open wounds to contaminated water . However, epidemiological investigation should focus on the objective cause of the change of working environment. Furthermore, common diseases can possibly enhance the virulence of non-O1/non-O139 serogroups by attacking the tight junction of small intestinal epithelial cells, further triggering bacteremia, a process that may lead to death within 48–72 hours, which requires great attention.